PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BOOK BERBASIS KOMIK MATERI HAK DAN KEWAJIBAN KELAS IV SDN BULUSARI 3 - Zahra Putri Maulinda; Frans Aditia Wiguna; Kharisma Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study and development aims to evaluate the validity, feasibility, and efficacy of comic-based digital learning media about the rights and duties for fourth-grade students at SDN Bulusari 3. This study employs the Research and Development (R&D) methodology utilizing the ADDIE model, which has five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. This research involved 25 students from class IV at SDN Bulusari 3. The employed data analysis methodologies were qualitative descriptive analysis and quantitative descriptive analysis. The findings of this investigation suggest that. The validity test findings indicated a validation score of 88% from the material expert and 88% from the media expert, resulting in an average of 88%, categorized as extremely valid. The outcomes of the teacher's practicality assessment were 100%. The student practicality questionnaire yielded an average score of 92%. The two numbers were combined to get a score of 96%, based on the requirement of high practicality. The short trial efficacy test yielded an average score of 86.6%, whereas the assessment question score from the complete trial averaged 88%. The two numbers were aggregated, yielding a percentage of 87.3%, classified as extremely effective. The Development of Digital Book Learning Media Based on Comics for the Rights and Obligations of Class IV SDN Bulusari 3 has been deemed legitimate, practical, and effective.